2019
DOI: 10.1161/jaha.119.013267
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mineralocorticoid Receptor Antagonists on Atrial Fibrillation Occurrence: A Systematic Review, Meta‐Analysis, and Meta‐Regression to Identify Modifying Factors

Abstract: BackgroundMineralocorticoid receptor antagonists (MRAs) have emerged as potential atrial fibrillation (AF) preventive therapy, but inconsistent results have been reported. We aimed to examine the effects of MRAs on AF occurrence and explore factors that could influence the magnitude of the effect size.Methods and ResultsPubMed, Embase, and Cochrane Central databases were used to search for randomized clinical trials and observational studies addressing the effect of MRAs on AF occurrence from database inceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Although these approaches have largely focussed on targeting atrial fibrosis and inflammation, there is emerging evidence that endothelial dysfunction is a promising new addition to this list. Angiotensin-converting enzyme inhibitors (ACE inhibitors)/angiotensin receptor blockers (ARBs), 83 mineralocorticoid receptor antagonists (MRAs), 84 and antioxidants (such as N-acetylcysteine and ascorbic acid) 85 have all been shown to reduce the risk of new-onset AF and AF recurrence in large metaanalyses. Statins reduce all-cause and cardiovascular mortality in AF, 86 despite no consistent reduction in AF burden or recurrence.…”
Section: Endothelial Dysfunction-a Promising New Therapeutic Paradigm?mentioning
confidence: 99%
“…Although these approaches have largely focussed on targeting atrial fibrosis and inflammation, there is emerging evidence that endothelial dysfunction is a promising new addition to this list. Angiotensin-converting enzyme inhibitors (ACE inhibitors)/angiotensin receptor blockers (ARBs), 83 mineralocorticoid receptor antagonists (MRAs), 84 and antioxidants (such as N-acetylcysteine and ascorbic acid) 85 have all been shown to reduce the risk of new-onset AF and AF recurrence in large metaanalyses. Statins reduce all-cause and cardiovascular mortality in AF, 86 despite no consistent reduction in AF burden or recurrence.…”
Section: Endothelial Dysfunction-a Promising New Therapeutic Paradigm?mentioning
confidence: 99%
“…Neefs et al demonstrated that the mineralocorticoid receptor antagonists (MRA), spironolactone, and eplerenone significantly reduce new‐onset AF and recurrent AF; MRA treatment can be considered an additive therapeutic strategy for AF 9 . Alexandre et al showed a significant overall reduction in AF occurrence in patients treated with MRA versus the control groups (OR 0.55; 95% CI, 0.44–0.70, p < .00001), with the greatest benefit shown with regard to recurrent AF episodes (OR 0.42; 95% CI, 0.31–0.59, p < .00001) 10 . The renin–angiotensin system (RAS) is involved in the genesis of arrhythmia by the following two mechanisms: the induction of atrial fibrosis and structural remodeling by mitogen‐activated protein kinase (MAPK) expression and a reduction of collagenase activity, and the induction of electrical remodeling by a shortening of the atrial effective refractory period (AERP) and the action potential duration 11 …”
Section: Discussionmentioning
confidence: 99%
“… 227 A recent meta-analysis of 7914 patients showed that aldosterone pathway blockade with MR antagonists limited AF recurrence and, to a lesser extent, prevented the new onset of AF. 228 Since NPs counter-balance RAAS, recombinant human NPs (e.g. nesiritide—recombinant BNP) combined with neprilysin inhibitors (e.g.…”
Section: Towards ‘Hormonal Therapeutics’ In Afmentioning
confidence: 99%
“…sacubitril, enhancing NP signalling) and ARBs (e.g. valsartan), denoted ARNi (currently approved for the heart failure management) 228 or synthetic modified NPs designed to preferentially enhance signalling via specific NPRs, may also have potential benefits for AF management.…”
Section: Towards ‘Hormonal Therapeutics’ In Afmentioning
confidence: 99%